Karunia Roh menurut 1 Korintus 12:8-11 dan Penerapannya pada Ibadah - Yopi Tolego; Herman Liud (Jurnal Salvation, 2022)
Abstract: This paper specifically discusses the gifts of the spirit in 1 Corinthians 12:8-11 and their application in worship. The methods used in writing this topic are qualitative methods with a literary study approach and an exposition approach to biblical texts. The result of this description in Greek uses the word: (didotai) which means to give, handing out, entrusting, giving back, putting, making and lifting. So the understanding of the "gift of the Spirit" is freely given from the Holy Spirit who is the Person of God. They can be in the form of physical blessings, or something spiritual. The purpose of gift-giving is to confirm God's word which shows God's power is more dominant than the powers of the universe. The gift of the believer as well as the development of faith manifested in worship, as well as the gift of the spirit play a role in the multiplication of believers in Jesus.Abstrak: Tulisan ini mengulas secara spesifik mengenai karunia-karunia roh dalam 1 Korintus 12:8-11 dan penerapannya dalam ibadah. Metode yang digunakan dalam penulisan topik ini adalah metode kualitatif dengan pendekatan studi literatur dan pendekatan eksposisi teks Alkitab. Hasil pada uraian ini dalam bahasa Yunani menggunakan kata: didotai (didotai) yang berarti memberikan, membagi-bagikan, mempercayakan, memberi Kembali, menaruh, membuat dan mengangkat. Jadi pengertian “karunia Roh” pemberian dengan cuma-cuma dari Roh Kudus yang adalah Pribadi Allah, kepada setiap orang percaya sesuai dengan rencanaNya. Pemberian-pemberian itu bisa dalam bentuk berkat-berkat jasmani, atau sesuatu yang rohani. Tujuan dari pemberian karunia untuk mengkonfirmasi firman Allah yang menunjukkan kuasa Allah lebih dominan dari kuasa-kuasa alam semesta. Pemberian karunia bagi orang percaya sekaligus pengembangan iman yang diwujbu-nyatakan dalam ibadah, serta karunia roh berperan dalam multiplikasi orang yang percaya kepada Yesus.